2009
DOI: 10.5032/jae.2009.04063
|View full text |Cite
|
Sign up to set email alerts
|

Employers' Perceptions of Recent Agricultural Communications Graduates' Workplace Habits and Communication Skills

Abstract: Agricultural communications programs should frequently review their curriculum to ensure students receive the highest quality of education possible (Akers, 2000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 5 publications
6
29
0
Order By: Relevance
“…Photography is a common core skill taught in undergraduate agricultural communications curriculum (Terry, Lockaby, & Bailey-Evans, 1995) and is considered by industry professionals to be an important skill for graduates of agricultural communications programs (Terry & BaileyEvans, 1995;Irlbeck & Akers, 2009;Morgan, 2010). Understanding of photography and camera functions are also considered valued competencies by both agricultural communications alumni (Morgan, 2012) and faculty members (Morgan, 2013).…”
Section: Photography Instructionmentioning
confidence: 99%
“…Photography is a common core skill taught in undergraduate agricultural communications curriculum (Terry, Lockaby, & Bailey-Evans, 1995) and is considered by industry professionals to be an important skill for graduates of agricultural communications programs (Terry & BaileyEvans, 1995;Irlbeck & Akers, 2009;Morgan, 2010). Understanding of photography and camera functions are also considered valued competencies by both agricultural communications alumni (Morgan, 2012) and faculty members (Morgan, 2013).…”
Section: Photography Instructionmentioning
confidence: 99%
“…Despite their uncertainty, respondents reported that their organization had recruited and hired employees who had an agricultural communications major, and had worked with someone who had an agricultural communications major. Irlbeck and Akers (2009) found that agricultural communications professionals would like to see improvements among graduates in critical thinking and business etiquette. Even though NAMA members were unsure of graduates' skills coming out of college, agricultural communications students are sought after and are valuable to the agricultural communications industry.…”
Section: Conclusion Recommendations and Implicationsmentioning
confidence: 99%
“…One-on-one feedback sessions with an instructor facilitated students' development of writing skill and interpersonal communication skill in a Leggette et al (2015a) study as instructor and peer feedback helped students see their mistakes from another point of view leading to improved writing skill (Lea & Street, 1998). Rather than outlining specific communication skills, as others (e.g., Irlbeck & Akers, 2009;Morgan, 2010) have done, the broader points of skills education are a means for students to "learn to view their writing as someone else's reading" (Zamel, 1982, p. ab) and to develop authorial identity by learning to use language to communicate effectively (Hyland, 2002).…”
Section: Vector 1: Developing Competencementioning
confidence: 99%
“…Interpersonal relationships mediated by writing can assist with professional identity development (Murdock et al, 2013) because they promote a connection among students, their cohort, and their profession (Boyd, 2013). Characteristics of effective employees, such as trustworthiness and reliability (Irlbeck & Akers, 2009), can be enhanced through interactions with instructors, writing staff/mentors, and peers even though the relationship between students and teachers/peers can, at times, be detrimental to fostering strong interpersonal relationships that are often authoritative (Lea & Street, 1998).…”
Section: Vector 4: Mature Interpersonal Relationshipsmentioning
confidence: 99%